Urban transport infraestructure concessions in Chile - Gutiérrez, Héctor (Estudios de Economía, 2016)
To avoid the development of a congestion problem in roads and streets, the supply of transport infrastructure should keep pace with its demand. However, this is not an easy task, because the required funds tend to grow faster than tax collection does, which poses a challenge to Society: how to finance the gap between necessities and availabilities while not foreign a decrease in other sectors’ share in public budget, especially in social ones. For example, this paper argues that traffic management including the introduction of toll fees for the use of using congested streets or, in the extreme, the prohibition to use some cars in rush hours have limited potential to respond to the challenge. It seems there is no real alternative to just supply the infrastructure needed. In order to provide new or improved infrastructure, concessions have a potential to meet the challenge. On the one hand, the private sector may provide the money that the public sector does not have, and concession users pay for what they get in order to cover the investment (and a regressive subsidy is avoided). On the other hand, the private sector contributes with economic efficiency to enhance the provision of infrastructure, including new ideas, efficient investment and maintenance, and low toll fees. However, concessions pose an incentive compatibility problem which is not easy to solve. The paper elaborates on the Chilean way to solve the compatibility problem and recognizes the necessity to include bids for the lowest toll fees, to exclude government guarantees, and to reinforce property rights. The concession plan for Santiago is also presented.